Tension pyopneumothorax caused by Burkholderia cenocepacia: a rare case report in an immunocompetent individual - Shivam Garg; Madhusmita Mohapatra; Christie George Joseph; Maanasa Bhaskar (Monaldi Archives for Chest Disease, 2023)
Tension pyopneumothorax is a medical emergency that occurs when air and pus build up in the pleural space. This case report describes a 47-year-old diabetic female who presented with tension pyopneumothorax due to Burkholderia cenocepacia. The patient was successfully treated with a 24-French tube thoracostomy and antibiotics. To the best of our knowledge, this is the first case of tension pyopneumothorax caused by Burkholderia cenocepacia to be reported.